Vietnam industrial competitiveness report 2011 (United Nations Industrial Development Organization (UNIDO), 2011)
The report presented recommendations for the Vietnamese Government, including reformulation of industrial strategies and policies, industrial diversification into high value-added products, human resources development for manufacturing, technology development and targeting quality FDI for manufacturing.